Hydroxychloroquine therapy for women with both recurrent pregnancy loss and autoimmune disease: association with pregnancy outcomes and maternal-fetal complications - Du, Mengyang; Zhang, Ruixiu; Na, Yu; Peng, Liying; Bao, Shihua (Frontiers in Immunology, 2026)
ObjectiveTo evaluate the impact of hydroxychloroquine (HCQ) on pregnancy outcomes and maternal and fetal complications in women with a history of recurrent pregnancy loss (RPL) and autoimmune disease.MethodsThe medical records of pregnant women with a history of RPL and autoimmune disease attending the Shanghai First Maternity and Infant Hospital between January 2017 and December 2019 were retrospectively reviewed. Primary outcomes were gestational week at delivery (term: ≥ 37 weeks; preterm: < 37 weeks). Secondary outcomes were mid-to-late pregnancy loss and maternal and fetal complications, defined in accordance with national and international guidelines.Results103 (20.9%) patients were exposed to HCQ (0.1g twice daily), 389 (79.1%) were not. There were 436 full-term births, 48 preterm births, 5 late-term miscarriages, 2 stillbirths, and 1 fetal malformation-induced abortion. Univariable/multivariable analyses showed a potential protective trend of HCQ against preterm birth (unadjusted OR 0.86 [95% CI 0.40–1.84], p=0.70; Model 1 [adjusted for age, body mass index (BMI), recurrent abortion, antiphospholipid antibodies, undifferentiated connective tissue disease (UCTD)/Sjogren’s syndrome (SS), serological markers]: OR 0.59 [95% CI 0.19–1.84], p=0.37; Model 2 [additional adjustment for low molecular weight heparin (LMWH), intravenous immunoglobulin (IVIG), prednisone, aspirin]: OR 0.41 [95% CI 0.11–1.51], p=0.18). Fetal weight (HCQ: 3215.46 ± 459.21g vs. non-HCQ: 3226.96 ± 500.01g, p=0.84) and maternal-fetal complications showed no differences. Subgroup analysis stratified by autoimmune diagnosis (antiphospholipid syndrome [APS], UCTD, SS) revealed no heterogeneity (APS: OR 0.78 [95% CI 0.28, 2.22], p = 0.64; UCTD: OR 0.52 [95% CI 0.15, 1.81], p = 0.30; SS: OR 1.03 [95% CI 0.12, 8.87], p = 0.98).ConclusionThis study showed that in women with a history of RPL and autoimmune disease, HCQ use was not statistically significantly associated with adverse pregnancy outcomes or maternal-fetal complications. A potential protective trend against preterm birth was observed, but this association did not reach statistical significance.